Unlocking the Mystery: Comprehensive Analysis and Insights on Strengthening Organizational Defense - Mohanty, Biswajita (Journal of Research in Science and Engineering, 2025)
This paper comprehensively analyzes the attacks and intrusions by the Lapsus$ group. Lapsus$ is notorious for its high-profile attacks on major corporations and governmental entities. This study dives into the modus operandi of Lapsus$ and their tactics, techniques, and procedures (TTPs). This paper analyzes notable cyber compromises to produce actionable insights for organizational cybersecurity enhancements. This research examines case studies of Lapsus$'s significant attacks, including the intrusions into Okta, NVIDIA, and Microsoft, to understand the group's operational patterns, target selection, and the sophisticated nature of its campaigns.